Effect of Horizontal Eccentricity on the Response Reduction Factor (R) - Haya Bustami (جامعة النجاح الوطنية, 2025)
Structural irregularities significantly affect the seismic performance of buildings. Structures with architectural flaws may endure excessive twisting, differential story displacements, and probable collapse during seismic events. International standards, including ACI and ASCE, lack explicit directives for including the response modification factor (R) in the presence of horizontal eccentricity cases. The study aims to examine the impact of horizontal irregularity on the R factor for Intermediate Moment Resisting Frame (IMRF) structures. The study examines two variables: the number of stories and the amount of eccentricity. The study encompasses structures of 5, 7, 9, 12, and 15 stories, exhibiting eccentricity indicator values that vary from zero for reference specimens to 60% of the building width. SAP2000 is utilized for the analysis and design of buildings, incorporating response spectrum nonlinear analysis for seismic forces in accordance with ASCE standards. Push-over curves are produced to ascertain the correlation between horizontal eccentricity and R-value. Diverse push-over curves are utilized to examine various conditions. This encompasses standard push-over curves with flexural hinges, push-over curves incorporating mixed flexural, shear, and torsion hinges, as well as push-over curves reflecting the influence of bidirectional lateral pressures (push-over modal curves). The results demonstrate that the R-factor for the reference building corresponds with the recorded code value. Moreover, elevated eccentricity levels diminish the R-factor for buildings of identical height. As the elevation of the structure rises, the R-factor diminishes. The R-factor reduction varies from zero for the reference specimens to 25% for a fifteen-story with 60% eccentricity indicator. Utilizing bidirectional push-over curves that integrate integrated flexural, shear, and torsion hinges results in a 30% reduction in R-factors. For the majority of moderately tall structures, the reduction is approximately 15%. The decrease in the R-factor results from the development of plastic hinges on one side of the structure, causing abrupt failure of specific joints before the joints on the opposite side give.
تأثير الانحراف الافقي في المبنى على معامل الاستجابة الديناميكية المرنة للهياكل الخرسانية